Examining conjoint behavioral consultation to support students in middle school with social, emotional, and behavior concerns. Issue 183 (19th September 2022) - Garbacz, S. Andrew; Kaul, Megan; Zahn, Miranda; Godfrey, Eliza; Flack, Caleb
Abstract: The purpose of this study was to conduct a small‐scale pilot study of Conjoint Behavioral Consultation (CBC), modified for middle school students with social, emotional, and behavioral concerns. Participants were 30 middle school students with social, emotional, and behavioral concerns, along with their parents and teachers. Participants were randomized to a CBC or school‐as‐usual control condition. Outcome measures included (a) teacher‐report of student academic enablers and social, emotional, and behavioral competencies; (b) parent‐, teacher‐, and student report of target behavior outcomes; (c) parent‐ and teacher‐report of the parent‐teacher relationship; and (d) parent‐ and teacher‐report competence in problem‐solving. In addition, parents, teachers, and students reported their perceptions of the intervention. Findings suggested greater improvements in the intervention condition relative to the school‐as‐usual condition on teacher‐report of student interpersonal skills, teacher‐report of the parent‐teacher relationship, and parent‐report of competence in problem‐solving. In addition, parents, teachers, and students reported improvements in the target behavior outcomes during the consultation and each stakeholder rated the intervention favorably. Limitations, future research directions, and implications for family–school interventions in middle school are discussed.